Experimental trial on efficacy of cloxacillin as dry cow therapy and 0.5% iodine as premilking and postmilking teat dipping to reduce bovine mastitis - Thakur, Rabindra (2004)
The efficacy of dry cow therapy, pre and postmilking teat dipping for bovine mastitis was studied. A total of 54 Holstein-Friesian late pregnant dairy cows on one farm in their third to tenth lactation were selected. Animals were randomly allocated to treatment and untreated control groups. At drying off, treatment group received 500mg cloxacillin as dry cow therapy (DCT), intramammarily. Iodine 0.5% as teat dip was applied at pre and postmilking. The DCT cured infected quarter, significantly (P<0.05) for Any organisms (Gram-negative and Gram-positive) and Staphylococcus aureus. Prevention of mastitis using DCT was not significant (P> 0.05). Self cure rates at cow level was 16%-50% and at quarter level was 16%-65% for Any organism, S. aureus, coagulase-negative staphylococcus and Other organism (Other than S. aureus and CNS), respectively. New infection rates at cow level were 0%-75% and at quarter level was 18%-32%. Teat dipping did not significantly prevent new cases of mastitis (P>0.05). The California mastitis test (CMT) positive was significantly reduced (P<0.05) in treated quarters. The mean colony forming unit (cfu) log10 was 2.88 ± 0.32 (mean ± standard error of the mean) in first month after calving, significantly lower (P<0.05) in comparison to dry off and control group (5.76 ± 0.24 and 5.63 ± 0.37), respectively. The percent efficacy of the DCT was 48.8%. In conclusion, DCT significantly cured infected quarters and teat dipping did not prevent new cases of mastitis.